Association Between Migraine and Dry Eye: A Systematic Review and Metaanalysis. Issue 6 (4th June 2022) - Chen, Hanlin; Chen, Aiming; Wang, Shibin; Zou, Minjie; Young, Charlotte Aimee; Zheng, Danying; Jin, Guangming
Abstract : Purpose: The purpose of this study was to assess whether migraine might be associated with the increased risk of dry eye disease and to determine the strength of the association between migraine and dry eye disease. Methods: We searched EMBASE, PubMed, Web of Science databases and China National Knowledge Infrastructure, WanFang, and VIP databases for studies that investigated the association between dry eye and migraine from inception to September 8, 2020. Relevant data were extracted by 2 investigators independently. Publication bias and heterogeneity were evaluated. Odds ratio (OR) and 95% confidence interval (CI) were computed by metaanalysis using random-effects models. Results: Of the 565 studies identified, 7 studies met the inclusion criteria and were included in this metaanalysis. Patients with migraine had significantly higher morbidity of dry eye compared with the control group (OR = 1.55; 95% CI = 1.32–1.82; P < 0.001). Subgroup analysis showed that the association between dry eye and migraine was stronger in hospital-based studies (OR = 1.97, P = 0.036) than population-based studies (OR = 1.42, P < 0.001). In addition, differences in geographic location and diagnostic criteria have no effect on the results. Conclusions: There was a significant association between dry eye and migraine. Patients with migraine are more prone to suffer from dry eye than subjects without migraine, and the association strength varies among populations studied.